PENTINGNYA PEMERIKSAAN GOLONGAN DARAH BAGI SISWA/SISWI SMA GUNA MENDAPATKAN PELAYANAN KESEHATAN YANG BERKUALITAS - Rosnita Sebayang; Pra Dian Mariadi (Jurnal Abdimas Musi Charitas, 2018)
Humans have reliable transportation which is blood. Blood can also give a person's identity, among others, through blood type. In addition to providing an identity to someone there are several other benefits from the examination of blood types such as to help monitor the diet, to help avoid certain diseases, to determine the risk of heart disease, to help prevent colon cancer, speed up the process of donating and receiving blood transfusions, help overcome fertility. Considering the importance of knowing one's blood type and based on a survey conducted by SMAN 1 Tanjung Sakti Lahat, there are still many who do not know their blood type. Blood type examination was carried out at SMAN 1 Tanjung Sakti Lahat in February 2017. Of the 54 students who examined blood types there were 23 students with a percentage of 42.6% who had blood type A, blood type B as many as 15 students with a percentage 27.8%, blood type AB as many as 5 students with a percentage of 9.2%, and students who have blood type O as many as 11 students with a percentage of 20.4%.